Implementation of Gender Inclusive Child Health Services in Mataram City: Challenges and Strategies - Raufina Riandhani Mulyoto; Hendika Dwinanda Wicaksana; Suci Muqodimatul Jannah (Sean Institute, 2025)
The provision of child health services is a key indicator of public health quality; however, access and utilization are often influenced by gender-related factors. This study examines the implementation of gender-inclusive child health services in Mataram City, focusing on policy and programmatic strategies. A qualitative descriptive approach with a case study method was employed. Data were collected through in-depth interviews with healthcare providers, parents, and policymakers, as well as direct observations in health facilities and a review of relevant policy documents and program reports. Data were analyzed using the SWOT framework (Strengths, Weaknesses, Opportunities, Threats). Findings indicate that although gender-sensitive policies and service guidelines exist, practical implementation remains uneven. Strengths include dedicated healthcare staff, ongoing community health programs, and strong local government support. Weaknesses involve limited gender-sensitive training for healthcare providers, cultural norms affecting service utilization, and disparities in access between boys and girls. Opportunities exist through enhanced public awareness campaigns, collaborative partnerships, and policy reinforcement, whereas threats arise from persistent social norms, resource constraints, and variability in service quality across facilities. The study concludes that improving gender-inclusive child health services in Mataram City requires enhanced provider training, consistent monitoring, community engagement, and integrated policy strategies to ensure equitable access and quality care for all children.